2019
DOI: 10.1017/s002531541900078x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of artisanal fisheries on the behaviour and social structure ofTursiops truncatusin the South-western Gulf of Mexico

Abstract: Behavioural plasticity in animals is tested whenever competitive interactions for space and/or food resources occur between wildlife and human activities. This study uses the concepts of operational and non-operational interactions between bottlenose dolphins (Tursiops truncatus) and artisanal fisheries in Alvarado, to search for differences in behaviour, age structure and group size. We conducted 20 surveys between 2015 and 2016, and recorded 64 groups by means of scan sampling from either a research boat or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Higher survival rates for resident individuals were indirectly assumed by Morteo et al (2012b), who showed that these animals interact less frequently with fisheries, when compared to non-residents, thus facing lower exposure to entanglements in fishing gear and retaliation measures by fishers. Therefore, although much lower survival estimates for the visitor fraction is largely based on a high proportion of dolphins permanently leaving the study area shortly after the sampling, it is likely that higher mortality for non-residents is also due to a greater risk of predation by sharks and higher risk of entanglement in fishing gear (Morteo et al, 2012b(Morteo et al, , 2014(Morteo et al, , 2017Rechimont et al, 2018;Morales-Rincón et al, 2019). The latter is supported by reports from recently stranded animals -recorded between 2002 and 2019 (decomposition code 1-3, according to Geraci and Lounsbury, 1993) -showing that fisheries-related injuries only occurred in individuals that had not been previously photographed in the study area (Fuentes Del Muro and Morteo, unpublished data, LabMMar-UV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher survival rates for resident individuals were indirectly assumed by Morteo et al (2012b), who showed that these animals interact less frequently with fisheries, when compared to non-residents, thus facing lower exposure to entanglements in fishing gear and retaliation measures by fishers. Therefore, although much lower survival estimates for the visitor fraction is largely based on a high proportion of dolphins permanently leaving the study area shortly after the sampling, it is likely that higher mortality for non-residents is also due to a greater risk of predation by sharks and higher risk of entanglement in fishing gear (Morteo et al, 2012b(Morteo et al, , 2014(Morteo et al, , 2017Rechimont et al, 2018;Morales-Rincón et al, 2019). The latter is supported by reports from recently stranded animals -recorded between 2002 and 2019 (decomposition code 1-3, according to Geraci and Lounsbury, 1993) -showing that fisheries-related injuries only occurred in individuals that had not been previously photographed in the study area (Fuentes Del Muro and Morteo, unpublished data, LabMMar-UV).…”
Section: Discussionmentioning
confidence: 99%
“…The bottlenose dolphin has been widely documented in some localities in the southern GoM (Ortega Ortiz, 2002;Ortega Ortiz et al, 2004;Ramírez-León et al, 2020), including waters off the Tamiahua Lagoon System (Galindo et al, 2009;Martínez-Serrano et al, 2011;Valdés-Arellanes et al, 2011); Nautla (Morteo et al, 2019); and the Alvarado Lagoon System (ALS) in Veracruz state (Morteo, 2011;Morteo et al, 2012bMorteo et al, , 2014Morteo et al, , 2017Morteo et al, , 2019Morales-Rincón et al, 2019), and some coastal areas in the states of Tabasco, Campeche and Yucatán (Delgado-Estrella, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Temporal patterns and social dynamics of these dolphins show different habitat use and associations between sexes, and the recurrent presence of groups of a single sex within the study area indicate a sexually segregated population, where putative females are more abundant than putative males (Morteo et al, 2014). Documented threats to the species off ALS involve vessel harassment (Morales-Rincon et al, 2019), bycatch, or intentional captures (Morteo et al, 2017) to use dolphin meat as bait for shark fisheries (Ortega-Argueta et al, 2005) and, until the year 2000, live captures for display in oceanaria (Alaniz Pasini & Rojas Ortega, 2007). Interactions between dolphins and local fishers are antagonistic due to routine depredation of catches directly from fishing gear, which causes economic loss to the local, artisanal fishery (Rechimont et al, 2018).…”
Section: Study Areamentioning
confidence: 92%
“…Documented threats to the species off ALS involve vessel harassment (Morales‐Rincon et al, 2019), bycatch, or intentional captures (Morteo et al, 2017) to use dolphin meat as bait for shark fisheries (Ortega‐Argueta et al, 2005) and, until the year 2000, live captures for display in oceanaria (Alaniz Pasini & Rojas Ortega, 2007). Interactions between dolphins and local fishers are antagonistic due to routine depredation of catches directly from fishing gear, which causes economic loss to the local, artisanal fishery (Rechimont et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation